Rainfall variability and the risk of climatic drought in the Tensift basin (Morocco) - El-Hawari, Jawad; El-Ghachi, Mohamed; Bouhafa, Youness; Sinbri, AbdEllatif (Journal of natural sciences, life and applied sciences, 2023)
Drought is a natural phenomenon whose impact is directly reflected on human activities in general and economic activities (agricultural, industrial), whose success is closely linked to water resources (surface, underground). Which means that any decrease in water intake rates will greatly threaten those activities, so the phenomenon of drought has become one of the most threatening natural risks to natural resources in Morocco. From this point of view, the aim of this study to demonstrate the impact of this phenomenon based on the temporal and spatial variation of rainfall data at the level of the Tensift basin during the period from 1972 to 2015 on the one hand. In addition, to study the phenomenon of drought using a statistical series of monthly rainfall consisting of three meteorological stations (Aghbalou, Chichawa, Adamna), which represent the three parts of the basin (upper, middle Basin and estuary). On the other hand, in the drought analysis in the studied area, we relied on the Standardized Precipitation Index technique calculated over several times. This allowed us to characterize the fluctuations of this phenomenon, which have become more pronounced over the past decades. As for the results, over the studied period (1972-2015), a significant difference was observed in the periods of drought at the studied stations, for example, 08 consecutive periods of drought were observed at Aghbalou Station, 11 consecutive periods of drought at Chichawa station, and then 09 consecutive periods of drought at Adamna station.
Keywords: Tensift basin; series of rains; drought; SPI; dry periods; wet periods